Two-layer model for the numerical simulation of oil spills over coastal flows - Echeverribar, Isabel; Brufau, Pilar; García-Navarro, Pilar (Jornada de Jóvenes Investigadores del I3A, 2021)
A one-dimensional (1D) numerical model for the simulation of oil spills in coastal flows is studied. A two-layer eulerian model is implemented. The main advantage of this model is the capability of solving the evolution of the oil layer, computing the oil depth and the velocity field.